Penguatan Kesadaran Hukum Masyarakat Kampung Wasur tentang Sistem Peradilan Pidana Anak melalui Program Edukasi dan Pelatihan - rahail, emiliana; B. Rahail, Emiliana; Kamariah (Astha Grafika, 2025)
Abstract This community service program aims to enhance the legal awareness of Wasur Village residents regarding the implementation of the Juvenile Criminal Justice System (SPPA) based on restorative justice principles. The community’s limited understanding of children’s rights within legal processes often results in the violation of those rights, both for child offenders and victims. The program was carried out through participatory legal education and training involving village officials, community leaders, teachers, and youth groups. The activities included legal seminars, interactive discussions, legal case simulations, and dissemination of educational media such as posters and videos. The results indicated a significant improvement in participants’ legal knowledge and a positive shift in community attitudes toward the concept of diversion in child case resolution. This program also strengthened collaboration between academics, village officials, and customary leaders in promoting a more humanistic and inclusive legal culture.